2017
DOI: 10.1101/148999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of polymorphisms in theP. falciparumartemisinin resistance markerkelch13in asymptomatic infections in a rural area of Cameroon

Abstract: Background. The genetic variability of the artemisinin resistance (AR) molecular marker

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This is consistent with previous reports conducted in Cameroon. To date, seven epidemiological-molecular studies had been conducted in Cameroon which showed a heterogeneity of mutations in the parasite population 10 years after the implementation of ACTs in the Centre and South West regions of the country [29,3234,41,42,51]. These studies indicated that less than 4% of all samples showed a mutation in the K13 gene and none were among those associated with artemisinin clearance delay in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with previous reports conducted in Cameroon. To date, seven epidemiological-molecular studies had been conducted in Cameroon which showed a heterogeneity of mutations in the parasite population 10 years after the implementation of ACTs in the Centre and South West regions of the country [29,3234,41,42,51]. These studies indicated that less than 4% of all samples showed a mutation in the K13 gene and none were among those associated with artemisinin clearance delay in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…In Central, West and East Africa, the allelic frequencies reported were generally rare less than 6% [24,27,34,36,49,52,53]. However, one study in Cameroon revealed a high rate, 15.1% of isolates presented at least one non-synonymous SNP in K13 gene [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 11 candidate gene polymorphisms associated with delayed parasite clearance [17,19,20]. A number of mutations have also been reported outside the K13 propeller region notably, K189T and E252Q [19,[21][22][23]. In Africa, the highest geographical distribution is A578S [18,19,24] and the presence of R561H mutation has recently been reported in Tanzania [25] and Rwanda [26].…”
Section: Introductionmentioning
confidence: 99%